Description of Antibiotic Use for Pediatric Pharyngitis Patients at Ibnu Sina YW-UMI Hospital, Makassar, 2022-2023 - Arsal, Andi Sitti Fahirah; Jaya, Rika Dwi; Irwan, Andi Alamanda; Darma, Sidrah; Darussalam, Andi Husni Esa (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Pharyngitis is inflammation of the pharynx, often caused by viral or bacterial infections, especially Group A beta-hemolytic Streptococcus in children. The Centor score helps identify bacterial cases. In Indonesia, respiratory tract infections account for 25% of illnesses, with Group A Streptococcus causing 5–36% of pharyngitis cases. Objective: To describe antibiotic use in pediatric pharyngitis patients at Ibnu Sina YW-UMI Hospital, Makassar, in 2022–2023. Methods: A retrospective study included patients aged 5–18 years diagnosed with pharyngitis. Data on age, sex, antibiotic type, and treatment duration were collected. Results: Seventy-one patients were analyzed; most were aged 5–9 years (50.7%) and male (66.2%). The most common treatment duration was 4 days (25.4%). Cephalosporins were the most used antibiotics, particularly 3rd generation (76.1%). Ceftriaxone was most prescribed (39.4%), followed by combination antibiotics (32.4%) and other cephalosporins like cefadroxyl and cefixime (8.5% each). Conclusion: Pediatric pharyngitis predominantly affects males aged 5–9 years. The average treatment duration is 4 days, with 3rd-generation cephalosporins, especially ceftriaxone, being the most commonly used antibiotics